Method for measuring extrusion power index of material

By introducing the measurement method of material extrusion work index into the material bed crushing technology, the complex and time-consuming problems of traditional methods are solved, and the accurate evaluation and prediction of material fragility and equipment working parameters are achieved, which improves the application efficiency and accuracy of material bed crushing technology.

CN119901577AActive Publication Date: 2025-04-29CNBM (HEFEI) POWDER TECHNOLOGY EQUIPMENT CO LTD

Patent Information

Application Number
CN202510084302.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The prior art has defects in the evaluation of the fragility of material bed crushing materials and the prediction of production parameters. The traditional method is complex in operation, large in materials, long in time, and the test results need to be greatly corrected, so it is impossible to effectively predict the working parameters of roller presses and other equipment.

Method used

A method for measuring material extrusion work index is provided. By taking the material to be tested for extrusion and crushing, the fine powder increment after extrusion is calculated, and the extrusion work index is calculated according to a specific formula to predict bench-top output and equipment working parameters.

Benefits of technology

This method simplifies operation, reduces material consumption, can accurately evaluate the difficulty of material crushing, accurately simulate the production process, effectively predict equipment working parameters, and reduce test costs and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119901577A_ABST
    Figure CN119901577A_ABST
Patent Text Reader

Abstract

The invention discloses a material extrusion power index determination method, which comprises: taking a material to be determined, and carrying out screen analysis to obtain a fine powder content percentage e0 in the material, and a corresponding sieve pore size when 80 w.% of the material to be determined passes through; the particle size of the fine powder is not greater than Pi; taking a to-be-detected material, extruding and crushing to obtain a material cake; scattering the material cake, carrying out screen analysis to obtain fine powder and coarse powder, and calculating the increment of the extruded fine powder; reserving a sample of the fine powder obtained in the step S2 for later use, and supplementing a measured material with the same mass as the fine powder into the coarse powder; repeating the steps S2-S3 for at least three times until the system reaches a balanced and stable condition; keeping fine powder in the material after the system is balanced and stabilized, uniformly mixing and carrying out screen analysis to obtain a corresponding sieve pore size when 80w.% of the fine powder passes through; and calculating the extrusion power index according to the data. The method solves the problems that the productivity of the material bed crushing equipment such as the roller press is difficult to predict, the prediction means of the production process is lacked and the like, and has important theoretical significance and practical value for the fundamental research of the material bed crushing technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material bed crushing, in particular to a method for measuring a material extrusion work index. Background Art

[0002] In the field of materials processing, comminution technology, particularly bed comminution, has always been a key component, and its importance has grown with the development of modern industry. Since the 1980s, high-pressure bed comminution technology has emerged, and grinding equipment such as roller presses and vertical mills have been widely used. These technologies offer significant advantages, such as high fine particle content, numerous microcracks, and low energy consumption per unit of crushing. These technologies align with the trend toward "more crushing, less grinding" and have become a core technology for improving comminution efficiency.

[0003] However, in the research and application of bed pulverization technology, evaluating material friability and predicting related production parameters remain pressing challenges. Traditional laboratory-scale interlayer pulverization testing methods for particle beds have numerous drawbacks. Semi-industrial or small roller press pulverization tests are complex, require large amounts of material, are time-consuming and labor-intensive, and require significant revisions before they can be applied to industrial design, significantly limiting their widespread use in experimental research. Grindability and laboratory Bond work tests are based on ball mills, which are single-particle pulverization devices that operate very differently from bed pulverization equipment like roller presses. These tests yield significant errors for materials that are easily grinded but difficult to crush. This often leads to significant deviations from actual production results in basic bed pulverization research and industrial capacity and power consumption predictions for production lines using bed pulverization equipment. For example, in the cement industry, when Bond work index tests are used to guide production, their pulverization principles differ from those of roller presses and vertical mills used in actual production, significantly reducing their value as a reference for equipment selection and process design.

[0004] While the pellet bed piston ballast test can initially simulate the material bed pulverization process and provide some predictions about the operating parameters of equipment like roller presses, it has significant shortcomings. For one thing, the applicability of its model and empirical formula requires extensive verification. Furthermore, traditional piston ballast tests complete pulverization with only a single load, significantly different from the continuous pulverization process of a high-pressure roller mill. Furthermore, most studies focus solely on pulverization energy consumption or product particle size prediction, with limited consideration of other key parameters for equipment selection and process design. Consequently, a comprehensive, intuitive, and feasible experimental methodology for studying pellet bed pulverization has not been established. While the POLYCOM Grinding Index (PGI) test developed by Thyssen Krupp Polysius in Germany can determine a material's suitability for high-pressure roller mill pulverization, it requires a large amount of ore, is complex, labor-intensive, time-consuming, and expensive, creating significant challenges for practical application.

[0005] To sum up, the existing technology has defects in the evaluation of the friability of materials in bed crushing and the prediction of production parameters. There is an urgent need for a new measurement method and device that can be compatible with the mechanism of bed crushing equipment, easy to operate, requires less material, and can accurately evaluate the difficulty of material crushing, and then effectively predict the working parameters of equipment such as roller presses, providing strong support for the development of bed crushing technology. Summary of the Invention

[0006] The purpose of the present invention is to provide a method for determining the extrusion work index of a material, so as to solve the problems of difficulty in predicting the production capacity of material bed crushing equipment such as roller presses and lack of prediction means for the production process, and has important theoretical significance and practical value for the basic research of material bed crushing technology.

[0007] To achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention discloses a method for determining the extrusion work index of a material, comprising the following steps: S1. Take the material to be tested and sieve to obtain the percentage of fine powder content e0 and the corresponding sieve hole size when 80w.% of the material to be tested passes through; wherein the particle size of the fine powder is not greater than Pi; S2. Extruding and crushing the material to be tested to obtain a cake; breaking up the cake and sieving to obtain fine powder and coarse powder, and calculating the fine powder increment after extrusion; S3, keeping a sample of the fine powder obtained in step S2 for later use, and adding the measured material with the same mass as the fine powder to the coarse powder; S4, repeat steps S2 to S3 at least three times until the system reaches equilibrium stability; S5. Retain the fine powder from the material after the system is balanced and stabilized, mix it, and sieve it to obtain the sieve hole size corresponding to the sieve through which 80% by weight of the fine powder passes; S6. Calculate the extrusion work index according to the following formula:

[0008] Where, E i is the extrusion work index, unit is kWh / t; e is the mass percentage of the fine powder increment in the total fine powder after extrusion equilibrium; G e is the average of the last three fine powder increments before the system is balanced, in g; F 80 The sieve size corresponding to the passage of 80w.% of the material to be tested, in µm; P 80 It is the sieve aperture size corresponding to the passage of 80w.% of the fine powder after the system is balanced and stabilized, in µm.

[0009] A further solution includes step S7: The predicted benchtop yield is calculated using the following formula: T2=T1* Ei1 / Ei2 Wherein, T1 is the benchtop output of the material to be tested, in t / h; Ei1 is the extrusion work index of the material to be tested, in kWh / t; T2 is the benchtop output of the replacement material, in t / h; Ei2 is the extrusion work index of the replacement material, in kWh / t.

[0010] Further solution: In step S2, the fine powder increment after extrusion is calculated according to the following formula: G ej =m j -m j-1 *e0, Where G ej is the increment of fine powder in the material after the jth extrusion, m j is the amount of fine powder after the jth extrusion, m j-1 is the amount of fine powder after the j-1th extrusion, e0 is the percentage of fine powder content obtained by sieving the material, and j is a natural number greater than 1.

[0011] Further solution: In step S4, the system reaches equilibrium stability condition: When the ratio of the difference between the maximum and minimum values ​​of the fine powder amount obtained three times in succession to the average value of the fine powder amount of the three times is ≤1%, the system reaches a stable state.

[0012] Further solution: The value of Pi is 45-200µm.

[0013] Preferably, the value of Pi is 80µm.

[0014] Further solutions: 80 and P 80 All are calculated by interpolation method.

[0015] Further solution: in step S2, the extrusion force is 800-1200 kN.

[0016] In a second aspect, the present invention discloses a computer-readable storage medium, on which are stored several acquisition and classification programs, which are used to be called by a processor and execute the method for determining the material extrusion work index as described in any one of claims 1-8.

[0017] Compared with the prior art, the present invention has the following beneficial effects: In terms of operation and material consumption, compared with traditional semi-industrial high-pressure roller mill or small roller press crushing tests, the present invention greatly reduces the amount of materials used, and the operation process is simple and efficient, which greatly reduces the test cost and time cost, effectively solving the problems of traditional methods that are complex, consumable, and time-consuming, and is more conducive to widespread promotion and application in experimental research.

[0018] From the perspective of crushing mechanisms and production simulation, the extrusion work index test is highly consistent with the crushing mechanisms of bed-type crushing equipment such as roller presses and vertical mills, accurately simulating the closed-loop production process and the material layer crushing process. Through actual material crushing and subsequent detailed screening, the test data obtained can truly reflect the changes in material characteristics under bed-type crushing conditions.

[0019] The advantages of the present invention are particularly prominent in terms of equipment parameter prediction and production regulation. Based on the measured extrusion work index, the particle size of the finished product after extrusion and crushing by the roller press can be accurately estimated, providing a key reference for product quality control; it can effectively predict the unit production of the roller press, helping enterprises to rationally plan production scale and progress; at the same time, the prediction of power consumption and power usage helps to optimize the energy allocation in the production process, achieve energy conservation, emission reduction and cost control. In the design and selection process of the roller press, the present invention provides a reliable theoretical basis, so that the equipment selection is more in line with actual production needs, improves the overall efficiency and stability of the production system, and comprehensively promotes the application and development of bed crushing technology in industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Flow chart of the assay method of the present invention; Figure 2 F is the material sieve size 80 Interpolation calculation diagram; Figure 3 is the material sieve size P 80 Interpolation calculation diagram; DETAILED DESCRIPTION The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0021] In the description of the present invention, it should be noted that the terms "upper", "lower", "left", "right", "inside", "outside", etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings, or are directions or positional relationships in which the inventive product is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction. Therefore, they should not be understood as limiting the present invention.

[0022] See also Figure 1 A method for determining the extrusion work value of a material is carried out according to the following steps: S1) Use a set of sieves to sieve 500g of the material to be tested (maximum particle size is 5mm) to obtain its particle size distribution, as shown in Table 1. According to Table 1, the percentage of fine powder content ≤Pi in the material to be tested is e0=14.91%, and the corresponding sieve size F when 80% of the mass passes through is 80 Obtained by interpolation method (see step S5); wherein Pi is taken as 80 μm; Table 1 Particle size distribution of the tested materials

[0023] S2) Take another 500g of the material to be tested, place it in the pressure testing machine, flatten it into the device and flatten the material, set the end loading force to 900kN, and squeeze and crush the material. When the loading force reaches the set value, unload the force and return the machine to complete the extrusion test; S3) Take the extruded material (cake) out of the pressure testing machine, break it up and sieve it with a sieve to obtain the amount of fine powder m1 and coarse powder (particle size > 80μm) in the extruded material M1 = 500-m1, where the fine powder increment G after extrusion is e1 =m1-m0*e; S4) The fine powder is kept as a sample for later use, and the material to be tested is added to the coarse powder in an amount equal to the weight of the fine powder removed, that is, the raw material weight m1 of the material to be tested is added to the coarse powder after the first extrusion, and the total weight of the extruded material is kept constant at m = 500 g. Steps S2-S3 are repeated until the equilibrium stable condition is reached: the increase in fine powder in the material after three consecutive extrusions (G en-2 , G en-1 , G en ) The difference between the maximum and minimum values ​​△G e and the average value of three times G e The ratio is ≤1%; the amount of fine powder before and after each extrusion is shown in Table 2; after the system is balanced and stable, the fine powder gradation is shown in Table 3; It can be seen from Table 2 that the system reaches equilibrium and stability after the 7th extrusion test; Table 2 Data on the amount of fine powder ≤80 μm before and after extrusion test

[0024] Table 3 Average gradation of fine powder ≤80 μm in the material after three consecutive balanced stable extrusions

[0025] S5) The fine powder ≤Pi in the material after balanced stable extrusion is mixed and sieved with a set sieve. The sieve hole size of the corresponding set sieve that 80% of the fine powder passes through is obtained by interpolation, i.e. P 80 ;like Figure 2 and Figure 3 As shown, by interpolation method F 80 and P 80 calculate: F 80 =5000-(99.60%-20%)*(5000-2500) / (99.60%-65.83%)=3549.01μm; P 80 =63-(90.08%-80%)*(63-54) / (90.08%-76.90%)=56.1μm; G e =(89.18+88.92+88.80) / 3=88.97g; △G e = (89.12-88.80) / 88.5 = 0.43%, meeting the equilibrium condition; e=(89.18+88.92+88.80) / (104.61+104.52+104.38)=85.13%; Substitute the above data into the formula to calculate the extrusion work index E of the material to be tested i1 : =4.09kWh / t.

[0026] Where, E i1 is the extrusion work index, kWh / t; e is the percentage of the fine powder increment ≤Pi in the total fine powder ≤Pi after the press extrusion material balance, e=(G en-2 +G en-1 +G en ) / (m n-2 +m n-1 +m n );G e is the average value of the fine powder increment ≤Pi after the last three consecutive extrusions are stable, g; F 80 and P 80 The sieve apertures corresponding to 80% of the initial material and product respectively, µm.

[0027] S6) Based on production data, the production capacity T1 of the material under test (i.e., material 1) was 261 t / h. However, after switching to material 2, the capacity dropped to 243 t / h. Material 2 was subjected to an extrusion work index test, with the same raw material gradation control as for material 1. The data from the press bed crushing test for material 2 are shown in Table 4. The average gradation of fine powder ≤80 µm in material 2 after system equilibrium and stabilization is shown in Table 5.

[0028] Table 4 Data of the press bed crushing test process of material 2

[0029] Table 5 Average gradation of fine powder ≤80µm in material 2 after three consecutive balanced and stable extrusions

[0030] Calculate the extrusion work index Ei2 of material 2: P80=63-(92.46%-80%)*(63-54) / (92.46%-77.25%)=55.63μm; △G e =(82.53+83.28+82.70) / 3=82.84g; e=(82.53+83.28+82.70) / (97.53+97.82+97.28)=84.92%; =4.08kWh / t.

[0031] By comparing the extrusion work indices Ei and Ei2 of the two materials, we can obtain the predicted output of material 2: T2=T1*Ei1 / Ei2=244.03t / h, which is basically consistent with the actual production situation.

[0032] Although this specification is described according to implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

[0033] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent modifications made according to the scope of the claims of the present application are within the scope of protection of the claims of the present application.

Claims

1. A method for determining the extrusion work index of a material, characterized in that: The following steps are involved: S1. Take the material to be tested, and sieve to obtain the percentage of fine powder content e0, and the corresponding sieve hole size when 80w.% of the material to be tested passes through; wherein, the particle size of the fine powder is not greater than Pi; S2, taking the material to be tested and extruding and crushing it to obtain a cake; breaking up the cake and sieving it to obtain fine powder and coarse powder, and calculating the fine powder increment after extrusion; S3, keeping a sample of the fine powder obtained in step S2 for later use, and adding the measured material with the same mass as the fine powder into the coarse powder; S4, repeat steps S2-S3 at least three times until the system reaches a stable equilibrium condition; S5. Retain fine powder from the material after the system is balanced and stabilized, mix and sieve, and obtain the sieve hole size corresponding to when 80w.% of the fine powder passes through; S6. Calculate the extrusion work index according to the following formula: In the formula, E i is the extrusion work index, in kWh / t; e is the mass percentage of the fine powder increment in the total fine powder after extrusion equilibrium; G e is the average of the last three fine powder increments before the system is balanced, in g; F 80 It is the sieve hole size corresponding to the passage of 80w.% of the material to be tested, in µm; P 80 It is the sieve hole diameter corresponding to the passage of 80w.% of the fine powder after the system is balanced and stabilized, in µm.

2. The method for determining the material extrusion work index according to claim 1, characterized in that: The step S7 is also included: The predicted benchtop yield is calculated according to the following formula: T2=T1* Ei1 / Ei2 Wherein, T1 is the benchtop output of the material to be tested, in t / h; Ei1 is the extrusion work index of the material to be tested, in kWh / t; T2 is the benchtop output of the replacement material, in t / h; Ei2 is the extrusion work index of the replacement material, in kWh / t.

3. The method for determining the material extrusion work index according to claim 1, characterized in that: In step S2, the fine powder increment after extrusion is calculated according to the following formula: G ej =m j -m j-1 *e0, In the formula, G ej is the fine powder increment in the material after the jth extrusion, m j is the amount of fine powder after the jth extrusion, m j-1 is the amount of fine powder after the j-1th extrusion, e0 is the percentage of fine powder content obtained by sieving the material, and j is a natural number greater than 1.

4. The method for determining the material extrusion work index according to claim 1, characterized in that: In step S4, the system reaches a stable equilibrium condition: When the ratio of the difference between the maximum and minimum values ​​of the fine powder amount obtained three times in succession to the average value of the fine powder amount of the three times is ≤1%, the system reaches a stable state.

5. The method for determining the material extrusion work index according to claim 1, characterized in that: The value of Pi is 45-200µm.

6. The method for determining the material extrusion work index according to claim 3, characterized in that: The value of Pi is 80µm.

7. The method for determining the material extrusion work index according to claim 1, characterized in that: The F 80 and P 80 All are calculated by interpolation method.

8. The method for determining the material extrusion work index according to claim 1, characterized in that: In step S2, the extrusion force is 800-1200 kN.

9. A computer-readable storage medium, characterized in that: The computer-readable storage medium stores a plurality of acquisition and classification programs, and the plurality of acquisition and classification programs are used to be called by a processor and execute the method for determining the material extrusion work index as described in any one of claims 1-8.

Citation Information

Patent Citations

  • Method for determining best grinding feed size

    CN104607301A

  • Determining method for static pressure work index of ore and device used in method

    CN104897470A

  • Testing method for ball mills

    CN1938096A

  • Method and apparatus for evaluating crushability

    JP1995260657A

Cited By

  • Method and system for separating and measuring effective crushing work and dissipated energy in material bed crushing

    CN121499109A